2021
DOI: 10.1161/str.52.suppl_1.p589
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P589: Pediatric Thrombectomy: Design And Workflow Lessons From Two Experienced Centers

Abstract: Introduction: While clinical trials have demonstrated the remarkable efficacy of endovascular thrombectomy (EVT) for treating adult patients suffering from acute ischemic stroke (AIS), benefits reaped from advances in adult stroke care have unfortunately not occurred in parallel with pediatric stroke care. Randomized trials of EVT in childhood stroke are unlikely given the low incidence of stroke in children compared to adults, and despite promising outcomes in small case reports and series, EVT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…As a result, few pediatric hospitals currently provide EVT, and most instead rely upon inter-hospital transport to an EVT center. 8 Though this care paradigm is widely used, the proximity of EVT hospitals to pediatric hospitals has not previously been characterized. We found that the majority of pediatric hospitals are within reasonable proximity of an EVT center.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, few pediatric hospitals currently provide EVT, and most instead rely upon inter-hospital transport to an EVT center. 8 Though this care paradigm is widely used, the proximity of EVT hospitals to pediatric hospitals has not previously been characterized. We found that the majority of pediatric hospitals are within reasonable proximity of an EVT center.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these opportunities have been highlighted in a recent publication describing strategies to improve coordination between pediatric and EVT hospitals. 8 One particularly relevant suggestion of this work is the introduction of adult-optimized workflows into pediatric stroke setting so that pediatric patients can benefit from well-rehearsed adult stroke workflows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Additional publications offer guidance on devices and other technical considerations, workflow, and pediatric stroke center requirements. [17][18][19]…”
Section: Acute Interventionsmentioning
confidence: 99%
“…Often, ambulances with adult stroke calls are diverted to these centres for acute management. If this is the case in your hospital, it is worthwhile engaging with the adult stroke specialists and their HASUs who will have expertise on implementation of adult stroke protocols 5. Some hospitals have already agreed to admit young people from 16 years (or younger in some cases) and up to the HASU for management if there is paediatric neurology input.…”
mentioning
confidence: 99%